Reachability testing algorithm for parallel program in heterogeneous network environment - WANG Wei1; DU Cui-lan2; ZHANG Hong-li1 (Tongxin xuebao)
Orienting to difficulty of testing nondeterministic parallel programs,the relationship between message-passing behavior and network performance constraint in grid environment was analyzed,and a new limited reachability testing algorithm was proposed,which was called reachability testing algorithm with network performance constraint,based on classic reachability algorithm.This algorithm only tested those execution paths with high happening possibility,which can reduce the number of those paths to be tested.The testing efficiency is improved,and the testing completeness is held reasonably.